A Novel Retinal Nerve Fiber Layer Biomarker of Amyotrophic Lateral Sclerosis (ALS) Identified Using Longitudinal in vivo Ocular Imaging - Khorrami F; Gupta N; Zhou X; Liang Y; Yucel YH (Eye and Brain)
Farbod Khorrami,1,2 Neeru Gupta,1– 5 Xun Zhou,1 You Liang,6 Yeni H Yucel1– 4,7– 9 1Keenan Research Centre for Biomedical Science, Li Ka Shing Knowledge Institute, St. Michael’s Hospital, Toronto, ON, Canada; 2Department of Laboratory Medicine and Pathobiology, Temerty Faculty of Medicine, University of Toronto, Toronto, ON, Canada; 3Department of Ophthalmology and Vision Sciences, Temerty Faculty of Medicine, University of Toronto, Toronto, ON, Canada; 4Department of Ophthalmology and Visual Sciences, University of British Columbia, Vancouver, BC, Canada; 5School of Population and Public Health, Faculty of Medicine, University of British Columbia, Vancouver, BC, Canada; 6Department of Mathematics, Toronto Metropolitan University, Toronto, ON, Canada; 7Department of Physics, Faculty of Science, Toronto Metropolitan University, Toronto, ON, Canada; 8Institute of Biomedical Engineering, Science and Technology (iBEST), St. Michael’s Hospital, Toronto Metropolitan University, Toronto, ON, Canada; 9Department of Mechanical Engineering, Faculty of Engineering and Architectural Science, Toronto Metropolitan University, Toronto, ON, CanadaCorrespondence: Yeni H Yucel, Ophthalmic Pathology Laboratory, Temerty Faculty of Medicine, University of Toronto, Keenan Research Centre for Biomedical Science, St. Michael’s Hospital, Unity Health Toronto, 30 Bond Street, 209 LKSKI, Room 409, Toronto, ON, M5B 1W8, Canada, Tel +1 416 864-6060 - Ext: 77594, Email yeni.yucel@unityhealth.toPurpose: Like motor neurons, retinal ganglion cells (RGCs) have long axons and high metabolic demands, making them vulnerable to disruption of axonal transport. Unlike motor neurons, the RGC axons are accessible to high-resolution non-invasive optical imaging in their intraocular portion. A non-invasive in vivo retinal imaging biomarker can be valuable for amyotrophic lateral sclerosis (ALS) diagnosis and monitoring. We aim to assess the presence of inner retinal pathology in a mouse model of ALS and its possible progression with age.Methods: Transgenic SOD1G93A mice (n=8, 4M/4F) and age-matched controls (n=8, 4M/4F) underwent in vivo retinal imaging with confocal scanning laser ophthalmoscopy (cSLO) coupled with optical coherence tomography (OCT) at 20 weeks of age. Another group of SOD1G93A mice (n=20, 6M/14F) and age-matched controls (n=20, 6M/14F) underwent longitudinal in vivo retinal imaging with the same device. Each retinal imaging session included infrared reflectance (IR) and blue reflectance (BR) cSLO coupled with OCT. Hyperreflective puncta located in the retinal nerve fiber layer (RNFL) were counted in a blinded fashion in ALS and control mice. The number of puncta at 20 weeks of age in ALS mice was compared with controls using Wilcoxon test. The rates of increase of puncta number were analyzed using a Generalized Linear Mixed-Effect Model (GLMM) for genotype, time, and sex.Results: IR-cSLO coupled with OCT revealed hyperreflective puncta located in the RNFL of ALS mice. IR-cSLO fundus imaging at the age of 20 weeks showed ALS mice had significantly higher number of puncta compared to controls (2.1± 2.3 vs 0.5± 0.8; (mean±SD), respectively, p=0.036). GLMM analysis showed both ALS mutation and age were significantly associated with the rate of increase of puncta number (p=0.000232 and p=0.000366, respectively). In addition, female ALS mice had a steeper increase of puncta compared to male ALS mice (0.21± 0.04 log number puncta/week vs 0.16± 0.04, respectively; p=0.037).Conclusion: Our findings demonstrate distinct inner retinal nerve fiber layer pathology, detected using cSLO coupled with OCT, which worsens over time. These findings support the potential of retinal imaging as a translationally relevant, non-invasive biomarker for ALS diagnosis or disease monitoring in humans.Keywords: amyotrophic lateral sclerosis, retinal nerve fiber layer, superoxide dismutase, mouse, eye imaging, optical coherence tomography, sex, spheroids, pathology, hyperreflective, puncta